Effect of Cu particle size on hydrogenation of dimethyl succinate over Cu–SiO2 nanocomposite - Kasinathan, Palraj; Hwang, Dong Won; Lee, U-Hwang; Hwang, Young Kyu; Chang, Jong-San (Catalysis communications, 2013)
Copper–silica nanocomposite with different Cu particle size was synthesized by changing the concentration of Cu nitrate solution by precipitation-deposition method. In this preparation method, the average Cu particle size was estimated to be 11nm, 23nm and 33nm for 0.05M, 0.8M, and 2.0M of Cu nitrate solution, respectively, which was confirmed by XRD and TEM. When the catalytic activities of these materials, Cu(76)/SiO2, were compared in hydrogenation of dimethyl succinate (DMS) at 265°C and 25bar, the product distribution as well as DMS conversion was highly dependent on Cu particle size. At WHSV 0.4h−1, Cu(76)/SiO2 with Cu particle size of 11nm gave much higher tetrahydrofuran (THF) selectivity (93%) than that of 33nm (20%) for the same DMS conversion (100%). The smaller Cu particles size was more advantageous to higher DMS conversion and higher THF selectivity, while the larger Cu particle size was more advantageous to higher γ-butyrolactone (GBL) selectivity. It is concluded that THF could be produced selectively by controlling only Cu particle size without adding the acidic promoters such as alumina to Cu metallic sites. •Copper–silica nanocomposite with different Cu particle size was synthesized.•DMS conversion and product distribution was highly influenced by Cu particle size.•The smaller Cu particles size gave higher DMS conversion and THF selectivity.•Cu(76)/SiO2 (11nm Cu) showed 93% of THF selectivity at 100% DMS conversion.